Electrospun poly (lactic acid) -cotton core-shell yarns: Processing, morphology, and mechanical properties. (September 2022) - Maleki, Homa; Yilmaz, Demet; Semnani Rahbar, Rouhollah; Alay Aksoy, Sennur
In this study, aiming to improve the mechanical performance of the Poly (lactic acid) (PLA)-based nanofibrous structures, the electrospinning method was employed to develop twisted yarns with core-shell structure. Within this process, a conventional ring-spun cotton yarn fed to the electrical field, where nanofibers covered it by a certain orientation owning to the twisting procedure. This approach combines the excellent biological and physical-mechanical properties of cotton with outstanding features of the PLA nanofibers for biomedical applications. The effects of the core and shell structures on the ultimate properties of the electrospun core-shell yarns were investigated. Scanning electron microscopy (SEM) demonstrated that relatively uniform and bead-free fibers with smooth surfaces were formed. SEM images also confirmed that the nanofibers were arranged around the core with a specific angle to the axis (with the angle range of 8–44 based on the twisting rate) to constitute a twisted core-shell yarn. The diameter of the electrospun yarns decreased (∼ 22%) by increasing the twist rate. The influence of the core on the mechanical behavior of core-shell yarn are also discussed. Improvements in mechanical performance of core-shell yarns were generally perceived at low twist levels of the core yarn (αe = 2.8), and electrospun shell (40 rpm). Graphical Abstract